Extraction, Refining and Characterization of the Fixed Oil of Basil (Ocimumbasilicum L.) Seeds - Aburigal, Yasmin Adam; Modawi, Aisha A.; Elmogtaba, Elfadl Y.; Elsheikh, Fathelrahman A.; Hussein, Ismail H. (Gezira Journal of Agricultural Science, 2021)
Basil is considered one of the important medicinal and aromatic plants in Sudan and worldwide. It is very rich sources of phytochemicals which have vital properties affecting human health in reduce risks and diseases. The present study aimed to evaluate the physicochemical characteristics of basil seeds and the oil extracted from them. This included four accessions of basil grown in National Oil Seed Processing Research Institute (NOPRI) farm- University of Gezira- Sudan: (two local accessions of NOPRI and Umteraibat, and two accessions (Egyptian and Maldivian) obtained from Institute for Plant Genetics and Crop Plant Research (IPK), Gatersleben, Germany. Themethods used the American Oil Chemists Society (AOCS) official methods. The percentage of moisture content (4-5), oil content (19-28%), crude protein (15-20%), crude fiber (30-36%)and ash (5-8%)for basil seeds. The physical properties of crude oil were specific gravity at room temperature (0.92-0.93) and refractive index (1.4809-1.4823) at 20°C. The Lovibond readings for crude oil color were in the range (0.6-2.5) for the red color and (18-70) for the yellow color, while for the refined oil the red color was (0.2-0.5) and yellow was (2.5-6.2). Chemical properties were: free fatty acids for crude oil (0.2-0.76%) and (0.04-0.06%) for refined oil; peroxide and saponification values and the unsaponifiable matter were (5.7-24.9) ml.eqv.\kg, (195-198) mg KOH/g and (1.6-2.2%) respectively. The fatty acid composition was analyzed using GC-MS, and the percentage of the unsaturated fatty acids oleic, linoleic and linolenic were (0.78-2.13), (22.91-40.39%)and (22.83-39.32%)respectively; the most abundant saturated fatty acids were palmitic and stearic at (14.7-16.67%) and (9.18-11.57%) respectively.